Leading the Way: Indigenous knowledge and Collaboration at the Woolyungah Indigenous Centre - McGloin, Colleen; Marshall, Anne; Adams, Michael (Journal of University Teaching and Learning Practice, 2009)
This paper derives from collaborative research undertaken by staff at the Woolyungah Indigenous Centre, into our own teaching practice. It articulates a particular strand of inquiry emanating from the research: the importance of Indigenous knowledges as this is taught at Woolyungah in the discipline of Indigenous Studies. The paper is a reflection of Woolyungah’s pedagogical aims, and its development as a Unit that seeks to embed other knowledges into the realm of critical inquiry within subjects taught at the Unit. It also reflects student responses to our pedagogy. The writers are Indigenous and non-Indigenous and have collaborated with all teaching staff involved to present this work as a starting point for discussions about the emerging discipline of Indigenous Studies, its rigour as an academic field of inquiry and our commitment as educators to the inclusion of Indigenous knowledges in our programme.